KONTEKSTUALISASI PENAFSIRAN QS. AL-ḤUJURĀT [49]: 11 SEBAGAI RESPON TERHADAP FENOMENA CYBERBULLYING DI ERA DIGITAL - Ade Rosi Siti Zakiah; Luthfi Karimatun Nisa’; Laily Fitriani (Diya Al-Afkar: Jurnal Studi al-Quran dan al-Hadis, 2023)
The high number of cyberbullying in Indonesia is strongly influenced by the use of the internet which is increasing every year, especially among teenagers. In general, this action is carried out in various forms, whether on social media, online games, or platforms that provide columns for chatting. At the same time, the Koran records a number of incidents related to this phenomenon. The Qur'an does not explicitly mention the word cyberbullying, but in Surat al-Ḥujurāt verse 11 there is a word like yaskhar which means to make fun of and make fun of, then act arbitrarily or trouble other people. In particular, the main objective of this study is to explain how the contextual interpretation of QS. al-Ḥujurāt [49]: 11 and its relation to the phenomenon of cyberbullying in the digitalization era. This research is included in the category of library research with a normative-historical approach. The analysis theory used is Abdullah Saeed's contextual hermeneutics. As a result of this study, it was found that the text and context of QS. al-Ḥujurāt [49]: 11 shows that bullying behavior during the time of the Prophet saw was the same as bullying. This verse was revealed as an order in the form of a prohibition or categorized as an instructional value verse. There are fundamental values contained in this verse, including: the value of justice, the value of humanity and the value of responsibility. Tingginya angka cyberbullying di Indonesia sangat dipengaruhi oleh penggunaan internet yang meningkat setiap tahunnya terutama dikalangan remaja. Secara umum, tindakan ini dilakukan dalam berbagai bentuk, baik di media sosial, game online, maupun platform yang menyediakan kolom untuk chatting. Bersamaan dengan itu, al-Qur’an merekam sejumlah kejadian tentang fenomena tersebut. Al-Qur’an memang tidak menyebutkan secara eksplisit kata cyberbullying, namun dalam surat al-Ḥujurāt ayat 11 terdapat kata-kata seperti yaskhar yang berarti mengejek dan mengolok-olok, kemudian berlaku sewenang-wenang atau menyusahkan orang lain. Secara spesifik, tujuan utama penelitian ini untuk menjelaskan bagaimana penafsiran kontekstual QS. al-Ḥujurāt [49]: 11 dan kaitannya dengan fenomena cyberbullying di era digitalisasi. Kajian ini termasuk pada kategori penelitian kepustakaan (library research) dengan pendekatan normatif-historis. Teori analisis yang digunakan ialah hermeneutika kontekstual Abdullah Saeed. Sebagai hasil dari kajian ini, ditemukan bahwa teks dan konteks QS. al-Ḥujurāt [49]: 11 menunjukkan perilaku intimidasi pada masa Nabi Saw sama hal nya dengan tindakan bullying. Turunnya ayat ini sebagai perintah dalam bentuk larangan atau dikategorikan sebagai ayat instructional value. Terdapat nilai fundamental yang terkandung dalam ayat ini, antara lain: nilai keadilan, nilai kemanusiaan dan nilai tanggung jawab.